Examining Adherence With Recommendations for Follow-Up in the Prevention Among Colorectal Cancer Survivors Study - Hawkins, Nikki A. (Oncol Nurs Forum, 2015)
PURPOSE/OBJECTIVES: To explore the impact of health professionals’ recommendations for medical follow-up among colorectal cancer (CRC) survivors. DESIGN: Cross-sectional survey. SETTING: Mailed surveys and telephone interviews with CRC survivors in California. SAMPLE: 593 adults diagnosed with a primary CRC six to seven years before the time of the study. METHODS: Participants were identified through California Cancer Registry records and invited to take part in a survey delivered via mail or through telephone interview. MAIN RESEARCH VARIABLES: The survey assessed cancer history, current preventive health practices, health status, demographics, and other cancer-related experiences. FINDINGS: More than 70% of CRC survivors received recommendations for routine checkups, surveillance colonoscopy, or other cancer screenings after completing CRC treatment, and 18%–22% received no such recommendations. Recommendations were sometimes given in writing. Receiving a recommendation for a specific type of follow-up was associated with greater adherence to corresponding guidelines for routine checkups, colonoscopy, mammography, and Papanicolaou testing. Receiving written (versus unwritten) recommendations led to greater adherence only for colonoscopy. CONCLUSIONS: Most CRC survivors reported receiving recommendations for long-term medical follow-up and largely adhered to guidelines for follow-up. Receiving a health professional’s recommendation for follow-up was consistently associated with patient adherence, and limited evidence showed that recommendations in written form led to greater adherence than unwritten recommendations. IMPLICATIONS FOR NURSING: Given the increasingly important role of the oncology nurse in survivorship care, nurses can be instrumental in ensuring appropriate surveillance and follow-up care among CRC survivors. Conveying recommendations in written form, as is done in survivorship care plans, may be particularly effective.